A Critique of the Theory of Civil Liability of Aviation Operators: Focusing on Iranian Law and Jurisprudence and International Regulations - Ahmed Mozafari; Majid Banaeioskoei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In October 1929, in Warsaw, the Convention on the Uniformity of Aviation Regulations was signed by the participating countries and entered into force on 13 February 1933, following developments in the field of aviation and the occurrence of deficiencies in the text of the treaty. Twenty-five years later, the Warsaw Convention was amended on 28 September 1955 in The Hague, and the Protocol entered into force on 1 August 1963, with the most important change being the convention, which doubled the carrier’s liability. In 1975, the Iranian government acceded to the Warsaw Convention and its amended protocols and accepted the implementation of its regulations on foreign flights. In 1985, the Islamic Consultative Assembly considered the provisions of this treaty applicable to domestic flights. Many countries, such as Iran, acceded to the Warsaw Convention and its protocols. In the Iranian law, with the approval of the Law on Determining the Limits of Liability of Airlines in Iran on 5/11/2012, and despite the many criticisms leveled at this law, the amount of liability of domestic companies towards Iranian passengers on domestic flights is equivalent to ransom and what about foreign passengers. In domestic and international flights, it is equal to 16600 Sdr and in front of Iranian passengers in international flights, it is equal to 16600 Sdr. In this article, after presenting the common definitions in aviation law regarding the responsibility of transport operators and stating a history of a set of actions and documents, the principles of liability of the Convention and Iranian law were comparatively studied. The timing of the beginning and end of responsibility is one of the most important and challenging issues, which is discussed in detail in this article. The amount of damages payable is another chapter discussed in this article.